Tanggung Jawab Produk dalam Hukum Perlindungan Konsumen - Tami Rusli (Law Faculty of Universitas Bandar Lampung, 2012)
Weaken producer responsibility him to yielded product it and is important of him applying of product standardization in the effort improving product competitiveness and protection to consumer, queer and also the problems him in its him field so that it is important to know how product responsibility in consumerism law. Responsibility principle able to be gone into effect as effort to protect harmed consumer because usage of service or goods in practice can in the form of contractual responsibility, and product responsibility, Contractual responsibility can be applied by if perpetrator of is effort have done Wanprestasi. Product responsibility can be applied by if between perpetrator of is effort with consumer there no contractual relation and also in the case of deed contempt of court.